PROMOTING MATHEMATICAL CRITICAL THINKING SKILLS THROUGH PROJECT BASED LEARNING: A SYSTEMATIC LITERATURE REVIEW OF HIGH SCHOOL IMPLEMENTATION - Mardiana Mardiana; Mardiati Mardiati (Penelitian dan Pengembangan Ilmu, 2024)
This research examines implementation Project-Based Learning (PBL) in improving middle school students' mathematical critical thinking skills. The research objective is to identify strategies, challenges, and impacts of implementing PBL in the context of mathematics learning. The method used is Systematic Literature Review (SLR) with the PRISMA approach, analyzing relevant articles in the last ten years. The research results show that PBL is effective in improving critical thinking skills, especially when supported by technology and projects that are relevant to students' lives. The implications of this research include the importance of training for teachers and policy support to optimize the implementation of PBL in mathematics classes.